Potential of Cupressus lusitanica sawdust for pellet production using natural binding agents - Tantu, Tegene; Yadeta, Gemechu; Haile, Fikremariam; Tsegaye, Mahelete (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2026)
This study explored the potential of Cupressus lusitanica Sawdust for the production of pellets from carbonized sawdust using different natural binding agents (molasses, starch flour, fruit waste, and waste paper). The impacts of particle size and the type of binding agent used on the fuel qualities of pellets were investigated. The experimental results highlight that pellets produced from waste paper and starch flour binders exhibit high calorific values, high fixed carbon, and low moisture content. In contrast, molasses and fruit waste binders lower the fixed carbon and calorific value of pellets. As a result, the maximum calorific values were obtained using starch flour and waste paper, with respective values of 7052 and 7046 (cal/g). Maximum fixed carbon contents were 79.5% and 76.67% for waste paper and starch flour bonded pellets. Fruit waste and molasses binders result in lower calorific values, with respective values of 4831 cal/g and 5034 cal/g respectively. Pellets produced from fruit waste and waste paper showed lower ash contents of 1.53% and 1.67% respectively, indicating their environmental advantages. Therefore, starch flour, waste paper, molasses, and fruit waste are effective binders for biomass pellet production with improved quality.